HUBUNGAN KEPERCAYAAN DAN PERILAKU PERAWATAN TALI PUSAT PADA BAYI - Asmarani, Tuty -; Ilmiah, widia shofa (Universitas Muhammadiyah Ponorogo, 2024)
A newborn with complications is a newborn who has a disease or disorder that can result in disability or death, such as asphyxia, jaundice, hypothermia, neonatal tetanus/infection, birth trauma, BBLR, respiratory distress syndrome and congenital abnormalities, or who are included in the yellow list and red classification on Testing with Integrated Management of Young Infants (MTBM). This study uses a correlational research design with a cross sectional approach and the sample of this study is postpartum mothers who give birth to babies aged 1 – 15 days as many as 30 people using the purposive sampling method where samples are taken based on inclusion criteria. data collection using questionnaires and data in the analysis using frequency distribution with the Chi Square statistical test. In this study, it can be concluded that the result of P-Value .000 which means that there is a relationship of trust and behavior towards umbilical cord care in babies. . It is known that if trust is high, the behavior of umbilical cord care in babies will also be good